Análise do desempenho de uma microrrede com múltiplas unidades de geração distribuída - Silva, Flávio Lopes da (2011)
A microgrid has many benefits to the electric power system, especially when it comes to reliability of supply. Usually its microsources are alternative and renewable generations, which has attracted more investments for this type of power system. Thus, this work contributes to studies concerning microgrids, which is a new paradigm of Distributed Generation to the low voltage bus of the Electric Power System. In the beginning will be presented the concept of a microgrid and its main features, its main types of microsources, their advantages and disadvantages and their control topologies. The method of power control in a microgrid depends on the manner in which the microsource is connected to the low voltage bus, through inverters or rotating machinery. For performance analysis of an microgrid in adverse situations, a dynamic model is proposed. In this model, the microgrid is composed of several loads, a unit of energy storage and multiple generation units, which are: a photovoltaic module, a fuel cell, a microhydroelectric, a micro-thermoelectric and a wind generator. With this model, situations such as: connecting the microgrid to the distribution energy system, simulation of network failures and load variations within the microgrid can be analyzed.